Custos do trabalho: Uma análise da indústria brasileira no período 1996-2012 - Luiz Ricardo Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The aim of this work is to analyze the evolution and the composition of the labor costs in the industrial sector in Brazil during the period between 1996 and 2012. The source of data is the Annual Survey of Mining and Manufacturing Industries (PIA) issued by the Brazilian Institute of Geography and Statistics (IBGE). Labor costs comprise i) pay for time worked; ii) directly-paid benefits; iii) employer social insurance expenditures and labor-related taxes. This structure is compatible with the one adopted by the Bureau of Labor Statistics (BLS) and with the resolution concerning statistics of labor cost adopted by the International Labor Organization (ILO). It is shown that the monthly average labor costs per worker in the mining industry rose from BRL 4,165 to BRL 7,122 between 1996 and 2012 (in constant 2012 Brazilian Reais deflated by the Consumer Price Index - Broad Concept). As a result, the annual average growth rate reached 3.41% in the period. In the manufacturing industry, these costs rose from BRL 3,150 to BRL 3,582 in the same interval (annual average growth rate of 0.81%). When these costs are expressed in US Dollars and plotted in a graph the result is an "U-shape" curve, as the costs declined between 1996 and 2002 and, from this moment onwards, rose and reached a peak in 2011. This curve reflects the combined trajectories of the labor costs and of the exchange rates in the period. In 2012, the highest costs were observed in the "extraction of crude petroleum and natural gas" sector (BRL 36,729) whereas the lowest ones in the "manufacture of wearing apparel" sector (BRL 1,453). If the analysis is limited to the manufacturing industry, the highest costs were observed in the "manufacture of coke and refined petroleum products" sector (BRL 11,710). Considering both the mining and the manufacturing industries, employer social insurance expenditures and labor-related taxes represented, in 2012, around 25% of the total labor costs. There is, however, significant dispersion among sectors, as this percentage ranges from less than 20% to more than 30%.
Keywords: J3; 330; labor costs; mining and manufacturing industries; Brazil; social insurance expenditures; labor-related taxes